Acquisition of multipotent and migratory neural crest cells in vertebrate evolution. (August 2019) - Cheung, Martin; Tai, Andrew; Lu, Peter Jianning; Cheah, Kathryn SE
Abstract : The emergence of multipotent and migratory neural crest (NC) cells defines a key evolutionary transition from invertebrates to vertebrates. Studies in vertebrates have identified a complex gene regulatory network that governs sequential stages of NC ontogeny. Comparative analysis has revealed extensive conservation of the overall architecture of the NC gene regulatory network between jawless and jawed vertebrates. Among invertebrates, urochordates express putative NC gene homologs in the neural plate border region, but these NC-like cells do not have migratory capacity, whereas cephalochordates contain no NC cells but its genome contains most homologs of vertebrate NC genes. Whether the absence of migratory NC cells in invertebrates is due to differences in enhancer elements or an intrinsic limitation in potency remains unclear. We provide a brief overview of mechanisms that might explain how ancestral NC-like cells acquired the multipotency and migratory capacity seen in vertebrates.